Research and Application of Data Fusion and Data Mining in Early Warning Detection Intelligence Processing System. Issue 1 (1st October 2022) - Zhang, Zhixun; Shi, Ziyan; Liu, Jianhao; Du, Xinglin
Abstract : As a key technology of modern intelligence systems, Intelligence processing is a famous research area, and plays a basic role in the economy of the country especially in the early warning detection intelligence processing system. The basic theory of data fusion and date mining is comprehensively expounded, and real-time requirements of multi-target track data fusion, as well as offline demodulation timely information on characteristics of data mining, is deeply studied. Firstly, this paper discusses roundly the theory of association rules, which is an important research method of early warning intelligence data mining, proposes a new weighted probabilistic data association algorithm and improves joint probabilistic data association algorithm. Secondly, the knowledge of early warning intelligence data warehouse is detailed, and Law of cosines-text clustering algorithm based on distance is highlighted and extended. Finally, through the integration of real-time data integration and off-line data mining, the practical problems in information processing are effectively solved.